Novel Post‐Treatment Approaches to Tailor the Pore Size of PS‐b‐PHEMA Isoporous Membranes. Issue 18 (1st August 2018) - Wang, Jiali; Rahman, Md. Mushfequr; Abetz, Clarissa; Rangou, Sofia; Zhang, Zhenzhen; Abetz, Volker
Abstract: Using the example of an integral‐asymmetric isoporous membrane prepared from polystyrene‐ block ‐poly(2‐hydroxyethyl methacrylate) (PS‐ b ‐PHEMA), physical and chemical ways of post‐treatment are introduced with the aim to tailor the pore size. These post‐treatments are i) thermal annealing and ii) urethane chemistry of ethyl isocyanate (EI) in the presence of perfluoro(methyl cyclohexane). Via these approaches, the pore size of PS‐ b ‐PHEMA membranes is successfully tailored in the range of 10–20 nm with narrow pore size distribution by controlling the duration of thermal annealing and chemical reaction, respectively. The excellent hydrophilicity of the PS‐ b ‐PHEMA membrane is not changed by thermal annealing. The chemical postmodification using EI is associated with a loss of hydrophilicity with increasing conversion. Abstract : Polystyrene‐ block ‐poly(2‐hydroxyethyl methacrylate) (PS‐ b ‐PHEMA) membranes are fabricated by the combination of self‐assembly of block copolymers with nonsolvent‐induced phase separation. For the first time, the pore size of the PS‐ b ‐PHEMA membranes is tailored between 10 and 20 nm without destroying the isoporous structure by two post‐treatment routes: thermal annealing and urethane chemistry.